Limitations of the anticholinergic activity assay and assay-based anticholinergic drug scales - Wehran, Tanja; Kopitz, Jürgen; Plaschke, Konstanze; Weiß, Johanna; Seidling, Hanna; Haefeli, Walter E. (American journal of geriatric psychiatry, 2016)
The anticholinergic activity (AA) assay is a common method to determine a patient's anticholinergic load. Several limitations, however, are expected when applying the AA assay to patients or using drug scales to estimate anticholinergic burden based on AA levels. This study aims to demonstrate common pitfalls in an experimental setting and outline their clinical consequences. The AA was analyzed for five drugs with reported interaction with muscarinic receptors. Concentration-response curves were constructed for furosemide (weak anticholinergic), diphenhydramine (moderate anticholinergic), the strong anticholinergic amitriptyline and its metabolite nortriptyline, and the cholinergic pilocarpine. The Combination Index (CI) was used to assess the interaction of three drug combinations with amitriptyline. All compounds displaced the radioactive tracer from its receptor binding site in a concentration-dependent manner, and full displacement was reached for all compounds except furosemide (Emax 16%). The CI indicated that amitriptyline and thioridazine have antagonistic effects (CI = 1.46) at low and synergistic effects (CI = 0.88) at higher concentrations (p < 0.0001), whereas synergistic effects (CI = 0.47-0.48) were observed for amitriptyline in any concentration combined with pilocarpine (p < 0.001). When the patient's anticholinergic load is estimated using AA levels, the actual exposure, combination of anticholinergic drugs, their active metabolites, and also drugs with an opposite pharmacologic action will contribute to AA levels, whereas weak anticholinergic drugs in therapeutic concentrations are rather negligible.
Gesehen am 26.09.2017